2015
DOI: 10.1172/jci81321
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages mediate cardioprotective cellular postconditioning in acute myocardial infarction

Abstract: R e s e a R c h a R t i c l e 3 1 4 8jci.org Volume 125 Number 8 August 2015angioplasty to reopen the occluded coronary artery. After flow has been reestablished, the use of adjunctive therapy can be considered without distraction. Adjunctive cell therapy would require thawing of an allogeneic, off-the-shelf product and preparation for administration, which could introduce a delay of up to 20 minutes. Therefore, in our rat model, we subjected rats to 45 minutes of ischemia, followed by 20 minutes of reperfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
199
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(217 citation statements)
references
References 78 publications
13
199
0
5
Order By: Relevance
“…Thus, long‐term transplanted cell survival is not required for sustained benefit 32. Consistent with the mechanistic data in Figure 9F and 9G, our recent publication in a rat AMI model implicates CDC‐secreted exosomes in the mechanism of action, through effects on macrophage polarization 20…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, long‐term transplanted cell survival is not required for sustained benefit 32. Consistent with the mechanistic data in Figure 9F and 9G, our recent publication in a rat AMI model implicates CDC‐secreted exosomes in the mechanism of action, through effects on macrophage polarization 20…”
Section: Discussionsupporting
confidence: 82%
“…Allogeneic cell therapy has the additional advantage that it avoids variations of cell efficacy attributable to patient age or comorbidities, plus the risks and costs of patient‐specific tissue harvesting and cell processing. Although immune rejection is a possible disadvantage, allogeneic mesenchymal stem cells25 and CDCs (http://clinicaltrials.gov/ct2/show/NCT01458405) have been used in various early‐phase clinical trials of heart disease without safety concerns,25 consistent with preclinical studies indicating that allogeneic cell therapy without immunosuppression is safe and effective 3, 14, 20, 26. Indeed, our study demonstrates only nonsignificant local inflammatory response and the absence of circulating alloreactive antibodies with long‐term follow‐up after the administration of allo‐CDCs.…”
Section: Discussionmentioning
confidence: 82%
“…60 Interestingly, the mechanisms by which stem cells operate seem to have little to do with engraftment, as studies have shown little long-term persistence of infused or intramyocardially injected cells. 61 Rather, mechanistic studies in animals demonstrate that stem cells (and cardiospheres) seem to be taken up by resident cardiac macrophages, and that macrophages are required for the cardioprotective effects of stem cell therapy 62 ( Figure 2). In parallel to this association between stem cells and macrophages, a recent clinical trial expanded bone marrow-derived MSCs and activated macrophages (CD45 + CD14 + autofluorescent + ) ex vivo (Ixmyelocel-T) for subsequent intramyocardial injection in patients with chronic ischemic dilated cardiomyopathy.…”
Section: Stem Cell Therapy In Chronic Hf: An Immunomodulatory Mechanismmentioning
confidence: 99%
“…For example, in a mouse model of myocardial infarction, EV secretion is required for CDC efficacy, and CDC-EVs mimic the cardioprotective and regenerative effects of the parent CDCs [15]. Additionally, endogenous EVs figure prominently in cardioprotective paracrine signalling in mammals, in the process known as remote ischemic preconditioning [61]. In contrast to mammals, paracrine signalling in newts is poorly characterized.…”
Section: Discussionmentioning
confidence: 99%